Editorial Vol.2(2) - Regmi, Prakash Raj (Nepalese Heart Journal, 2003)
It is unfortunate that developing countries are fighting with both communicable and non-communicable diseases in large scales at the same time. Health problems are more complex as compared with the developed world. Poverty, population growth, lack of resources, low literacy rates, lack of trained manpower and basic health facilities at remote areas are making things more complicated.